Refiguring the Sacred Feminine : The Poems of John Donne, Aemilia Lanyer and John Milton - DiPasquale, Theresa M., 1962- (Book collections on Project MUSE., 2008)
"A study of the sacred feminine as it is understood in the works of John Donne, Aemilia Lanyer, and John Milton, each of whom reformed and envisioned several important Christian archetypes: Ecclesia, the Blessed Virgin Mary, Divine Wisdom, and the soul as bride of Christ"--Provided by publisher.